Practice of over-the-counter dispensary of antibiotics for childhood illnesses in Addis Ababa, Ethiopia: a simulated patient encounter study - Koji, Eyosait Mekonnen (Antimicrob Resist Infect Control, 2019)
BACKGROUND: Dispensary and use of antibiotics without prescriptions from qualified providers is a common practice in countries with poor pharmaceutical regulations and where due focus is not given to rational use. This practice is a main factor for the spread of antimicrobial resistance due to its non-reliance on pre-treatment microbiologic work-up, improper indications and dosing errors. This study was conducted to determine the rate of over-the-counter dispensary of antibiotics for common childhood illnesses among privately owned medicine retail outlets in Addis Ababa, Ethiopia. METHODS: Pre-determined simulated patient visits depicting common childhood illnesses were employed to request antibiotics without prescriptions. A simple random sampling was used to select medicine retail outlets within Addis Ababa city. Trained data collectors filled structured data forms (including antibiotic requested, reasons for denial of dispense and details enquired by pharmacist) shortly after each patient enactment. Multi-variable logistic regression analysis was employed to explore factors associated with over-the-counter sales of antibiotics. RESULTS: A total of 262 simulated encounters were surveyed. Of the 262 verbal antibiotic requests, 63.4% were dispensed. Close to 60% of encounters were accompanied by questions about a doctor’s visit or the child’s symptomatology while a past history of drug allergies was enquired in only 11.1% of visits. Over-the-counter dispensary was more likely when dispenser queried about symptoms was made (AOR: 2.412, 95%CI: 1.236, 4.706), for requests for more than one antibiotics (AOR: 2.988, 95%CI: 1.258, 7.095) and for simulated patient demands for oral antibiotics for children with acute diarrhea (AOR: 3.297, 95%CI: 1.248, 8.712) and parenteral antibiotics for those reported to receive in-patient care for pneumonia (4.516, 95% CI: 1.720, 11.857). CONCLUSIONS: The prevalence of providing antibiotics over-the-counter for pediatric illnesses in Addis Ababa is markedly high. Further studies into factors encouraging this malpractice are required. Enhancing education of personnel dispensing antibiotics and strict enforcement of national regulations are needed. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13756-019-0571-x) contains supplementary material, which is available to authorized users.